EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL SEBAGAI ALAT PROMOSI DI ERA GEN Z (Studi Kasus Pengguna Instagram di Kabupaten Pringsewu) - Irawan, Dedi; Syarifudin, Ahmad (STMIK Pringsewu, 2025)
This study aims to analyze the effectiveness of promotions through Instagram in increasing purchase decisions among Gen Z in Pringsewu. This study uses a qualitative approach with a case study method on Instagram users in Pringsewu. The research results show that Instagram is a highly effective promotional platform in increasing Gen Z's purchasing decisions in Pringsewu. The main factors influencing its effectiveness include content quality, the use of influencers, the level of interaction with consumers, and the utilization of Instagram Ads. An optimized digital marketing strategy will help build brand loyalty among Gen Z in Pringsewu. Thus, Instagram can become a highly effective tool in strengthening brand awareness and increasing sales in Pringsewu.